Sifat transmisi, pekali pupusan dan keterpantulan optik kepingan poli(metil metakrilat) (PMMA) didop dengan metil merah dan ferum (III) asetilasetonat - Mat Yunus, Wan Mahmood; Abd. Moksin, Mohd Maarof; Wan Yunus, Wan Md. Zin; Abdul Wahab, Noraini; Umam, Azizah (Universiti Putra Malaysia Press, 1999)
The optical transmission, reflection and extinction coefficient of a PMMA doped with methylene-red (PMMA-MM) and ferum (III) acetylacetonate (PMMA-FM) are presented. A rapid change of the optical transmission was observed in the range of wavelength (420-650 nm) and (500 - 600nm) for PMMA-FM and PMMAMM respectively. Eventhough the decrease of the optical transmission and the increase of the extinction coefficient do not linearly relate with increasing concentration of methylene-red and ferum (III) asetilasetonate, the transmission curve and the cut off transmission are still affected by doping concentration. It was found that the cut off value for PMMA-MM shifted from 200nm (for pure PMMA) to 550 nm when the concentration was increased to 6.3 31O-3mmol/g. A similar shift (200nm to 500nm) was also observed for PMMA-FM but with a higher doping concentration (i.e 30.7310-3 mmol/g).